2018
DOI: 10.1111/cbdd.13127
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of 9H‐fluorenone based 1,2,3‐triazole analogues as Mycobacterium tuberculosis InhA inhibitors

Abstract: We prepared fifty various 9H-fluorenone based 1,2,3-triazole analogues varied with NH, -S-, and -SO - groups using click chemistry. The target compounds were characterized by routine analytical techniques, H, CNMR, mass, elemental, single-crystal XRD (8a) and screened for in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Rv strain and two "wild" strains Spec. 210 and Spec. 192 and MIC was determined. Further, the compounds were evaluated for MTB InhA inhibition study as well. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Computational studies revealed strong binding with enoyl-acyl carrier protein reductase [53]. Heterocyclic hybrids of triazole inhibited MTB after binding with enoyl reductase (inhA) [54]. A virtual screening study against Mycobacterium N-acetylglucosamine -1-phosphate uridyltransferase discovered several compounds with a triazole nucleus and produced 20-60% inhibition of the enzymatic activity [55].…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies revealed strong binding with enoyl-acyl carrier protein reductase [53]. Heterocyclic hybrids of triazole inhibited MTB after binding with enoyl reductase (inhA) [54]. A virtual screening study against Mycobacterium N-acetylglucosamine -1-phosphate uridyltransferase discovered several compounds with a triazole nucleus and produced 20-60% inhibition of the enzymatic activity [55].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anionic forms of fluorene derivatives are often employed as effective ligands to transition metals, and some of these metal complexes can be used as catalysts for organic transformations including olefin polymerization . Furthermore, some fluorenes having a heteroatom substituent at their bridging carbon (9-position) are known to exhibit biological activity . Because of the high utility of this structural motif, various synthetic methods of fluorenes and their derivatives have been developed to date, but most of the existing methods rely on the use of intramolecular processes as exemplified in the classical Friedel–Crafts cyclization, radical cyclization, and more recent transition-metal-catalyzed cyclization involving C–H bond activation .…”
Section: Introductionmentioning
confidence: 99%